Predation by ants on jumping spiders (Araneae: Salticidae) in the Philippines - Thwaites, R.; Spanu, P.D.; Panopoulos, N.J.; Stevens, C.; Mansfield, J.W. (Scientific Societies, 2004)
Quantitative real-time polymerase chain reaction was used with specific TaqMan probes to examine transcription of selected hrp and effector genes in Pseudomonas syringae pv. phaseolicola strains 1448A (race 6) and 1449B (race 7). Transcripts examined were from genes encoding the regulators hrpR and hrpL, core structural components of the type III secretion system (TTSS) hrcC, hrcJ, hrcN, hrcU, and hrpA; the first open-reading frame of each hrp operon, including hrpF, hrpJ, hrpP, and hrpY; and also secreted effectors hrpZ, avrPphE, avrPphF, and virPphA. All genes were induced by incubation in a minimal medium and showed patterns of expression indicating regulation by HrpRS and HrpL. Basal mRNA levels and the timing of accumulation of transcripts after induction differed significantly, suggesting the operation of additional regulatory elements. However, no clear transcriptional hierarchy emerged to explain the ordered construction of the TTSS. Quantitative analysis confirmed that the rates and levels of transcript accumulation within the first 2 h after inoculation were considerably higher in planta than in vitro, and indicated that plant cell wall contact may enhance transcription of TTSS and effector genes in P. syringae pv. phaseolicola. The low-abundance hrcU mRNA had a half-life of 16.5 min, whereas other transcripts had half-lives between 3 and 8 min.